STUDI PROBABILITAS PEMILIHAN KERETA API PREMIUM SANCAKA (KA 97) DAN KERETA API PREMIUM MUTIARA SELATAN (KA 85) RUTE SURABAYA - YOGYAKARTA - Yoan Anjar Rinzani; Nugroho Utomo; Fithri Estikhamah (Racic : Rab Construction Research, 2024)
The train is a mode of transportation that continues to experience improvements in its services. PT. KAI has implemented the latest service, where all trains are equipped with air conditioning facilities. With these changes, each mode of transportation, particularly the Premium Sancaka Train and the Premium Mutiara Selatan Train, displays differences in characteristics such as ticket prices, travel time, and departure schedules. This study specifically selects the Premium Sancaka Train and the Premium Mutiara Selatan Train due to their closely scheduled departures. Therefore, the objective of this research is to determine the probability of train selection, necessitating a study related to factors that will be analyzed by distributing questionnaires and utilizing the Stated Preference method. From this study, significant results have been obtained regarding the likelihood of mode selection based on a ticket price difference of Rp. 20,000. The probability values for the Premium Sancaka Train (PKAS) and Premium Mutiara Selatan Train (PKAM) are 0.808 and 0.192, respectively. It can be concluded that respondents have a higher interest in the Premium Sancaka Train due to its lower ticket price. On the other hand, the probability of mode selection based on a travel time difference of -6 minutes shows values of 0.891 for PKAS and 0.109 for PKAM. Therefore, it can be concluded that respondents are more interested in the Premium Sancaka Train because it has a faster travel time